Chapter 25: Cole Crop Production in Florida - Stephen M. Olson; Eric H. Simonne; William M. Stall; Timur M. Momol; Susan E. Webb; Timothy G. Taylor; Scott A. Smith (EDIS)
This document is HS724, Horticultural Sciences Department, UF/IFAS Extension. Published November 2006.